CONTEMPORARY PEDAGOGICAL APPROACHES IN MUSIC EDUCATION: PLURALISM, ALTERNATIVE IDEAS, AND THE SOCIAL CONTEXT (Heritage, 2025)
This paper explores contemporary pedagogical approaches in music education through the lens of postmodern paradigms and educational pluralism, with particular emphasis on the integration of alternative educational methods into the formal education system of the Republic of Serbia. Based on the premise that music education is essential for the holistic development of students, the study reexamines the limitations of traditional, hierarchically structured teaching models and advocates for a more open, inclusive, and creative approach. The theoretical framework of the paper draws on critical, democratic, and postmodern pedagogical paradigms, relying on the works of Freire, Biesta, Hooks, and Dewey. These authors view education as a process of social transformation, dialogue, and empowerment of student subjectivity, which is particularly relevant in the context of arts education.The paper analyzes four significant alternative methods: Montessori, Waldorf, Suzuki, and Orff. Each method represents a distinct response to the need for a holistic student-centered approach, promoting individualization, creativity, musical sensitivity, and the experience of learning as a dynamic process. Special attention is given to the pedagogical goals, didactic tools, and practical applications of these methods, as well as their potential adaptation within the Serbian formal education system. Additionally, a comparative analysis of the education systems in Finland, Australia, and Slovenia is provided, highlighting examples of institutional support for pluralist and interdisciplinary approaches, along with successful integration of digital creativity and culturally relevant content in music instruction.Methodologically, the paper is grounded in qualitative analysis of theoretical and empirical literature, incorporating comparative insights. While positive examples of alternative pedagogical practices are identified in Serbia, the study also points out systemic challenges such as insufficient teacher training, lack of institutional support, and a rigid, traditional curriculum.In conclusion, the paper confirms the relevance of postmodern and pluralist orientations in music education, which enable more flexible, inclusive, and socially responsive teaching practices. The research questions posed are addressed through the synthesis of theoretical concepts, practical examples, and international comparisons. The paper offers specific recommendations for education policy and outlines directions for future research, particularly regarding the effects of hybrid pedagogical models on musical literacy, motivation, and intercultural competence among students.
Keywords: pedagogical pluralism, contemporary teaching, music education, alternative approaches.